1988
DOI: 10.1180/minmag.1988.052.368.10
|View full text |Cite
|
Sign up to set email alerts
|

Magmatic Garnets in the Cairngorm Granite, Scotland

Abstract: Small, euhedral Mn-rich garnets (32-52 mol. % spessartine) from the Cairngorm granite, Eastern Grampian Highlands, Scotland, are considered to be of magmatic origin and have not been derived from the assimilation of metasedimentary material, despite their occurrence largely at the margins of the pluton. Similar garnets also occur in a late cross-cutting aplite sheet. The garnets in the granite crystallized early in the sequence and are thought to have formed in response to the ponding of Mnrich fluids against … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 23 publications
(23 reference statements)
1
25
0
Order By: Relevance
“…In general, garnets from the Leinster lithium pegmatites have higher spessartine contents than those from Galway or Thailand. Garnets in peraluminous granites from Cairngorm (Harrison, 1988) and the Arabian Shield (du Bray, 1988) contain lower amounts of spessartine than the Aclare pegmatite-and aplite-hosted garnets. These data show that the chemistry of the pegmatite-hosted garnets from Aclare are typical of those in Li pegmatites (cf.…”
Section: Garnet Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…In general, garnets from the Leinster lithium pegmatites have higher spessartine contents than those from Galway or Thailand. Garnets in peraluminous granites from Cairngorm (Harrison, 1988) and the Arabian Shield (du Bray, 1988) contain lower amounts of spessartine than the Aclare pegmatite-and aplite-hosted garnets. These data show that the chemistry of the pegmatite-hosted garnets from Aclare are typical of those in Li pegmatites (cf.…”
Section: Garnet Chemistrymentioning
confidence: 99%
“…75-83 Copyright the Mineralogical Society a deeper insight into the origin and evolution of some granitic complexes (e.g. du Bray, 1988;Stone, 1988;Harrison, 1988). The presence and relative proportions of various garnet endmembers permit conclusions to be drawn about possible petrogeneses of granitic magma and also the approximate depth of formation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, many studies have shown that garnet in S-type granites can also be magmatic in origin (e.g. Allan and Clarke, 1981;Barnes et al, 2012;Dalquist et al, 2007;Harrison, 1988;Lackey et al, 2012;Villaros et al, 2009). In addition, when subjected to metamorphism at suitable conditions, granites may develop metamorphic garnet.…”
Section: Introductionmentioning
confidence: 99%
“…Well-formed and unzoned garnets are generally inferred to be phenocrysts (e.g. Green and Ringwood, 1968;Harrison, 1988), although original grain shapes may be modified by reaction with magma, particularly in the case of garnets transported to shallow structural levels during emplacement. Distinction of garnet phenocrysts and xenocrysts on textural grounds is hampered by the fact that xenocrysts also tend to be partly resorbed.…”
Section: Introductionmentioning
confidence: 99%